Triassic to Middle Jurassic geodynamic evolution of southwestern Gondwana: From a large flat-slab to mantle plume suction in a rollback subduction setting - Navarrete Granzotto, César Rodrigo; Gianni, Guido Martin; Encinas, A.; Marquez, Marcelo Jose; Kamerbeek, Constanza Belén; Valle, Mauro Nicolás; Folguera, A. (Earth-Science Reviews)
A novel geodynamic evolution model of the southwestern region of Gondwana from the late Triassic to the middle Jurassic period is proposed in this contribution, based on new data collected in the Patagonian region and an exhaustive bibliographic review. New geochemical data of La Leona Fm. (Deseado Massif) and a new zircon U/Pb age (207.6 + 4.1/−2.3 Ma), added to a compilation of previous geochronological and geochemical data, allow confirming the existence of an Upper Triassic magmatic arc in central Patagonia, with typical adakitic features. This volcanic arc developed about ~1000?1100 km away from the hypothetical paleo-trench (at its most distal portion) in and intraplate position. New geological mapping carried out in the surrounding areas of these arc-related products allowed recognizing an important and previously underestimated late Triassic contractional episode that affected the south-central Patagonian region, which can be correlated with multiple events of deformation in southwestern Gondwana as far as in the Cape and Sierra de la Ventana fold belts. After this contractional episode, the Jurassic Chon Aike Silicic Large Igneous Province (SLIP - Deseado Massif and North Patagonian Massif) outbursts from a crustal source linked to a mantle thermal anomaly, as new geochemical data and previous data indicate. New and previous structural, geochemical, and geochronological data allow us to propose the existence of a late Triassic-earliest early Jurassic flat-slab episode (~227?190? Ma), here referred to as the South Gondwanian flat-slab, comparable in size with the largest present and previously documented flat-slab configurations on Earth. This event would have been responsible for the inland arc migration, from a western position on the Antarctic Peninsula to central Patagonia (Central Patagonian Batholith), as well as the widespread contractional pulse registered in southwestern Gondwana. The existence of this late Triassic shallow subduction episode is reinforced by a combination of P-wave seismic ...